2015
DOI: 10.1111/jerd.12155
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different In Vitro Aging Methods on Color Stability of a Dental Resin‐Based Composite Using CIELAB and CIEDE2000 Color‐Difference Formulas

Abstract: Establishing the efficacy of different artificial aging methods and differences between color change using CIELAB and CIEDE2000 formulas are important to standardize color stability evaluations and facilitate the comparison of outcomes from different studies in the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
44
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 23 publications
3
44
0
4
Order By: Relevance
“…However, the CIEDE2000 (∆E 00 ) is more indicated for small color changes when compared samples that have colors close together [2,20]. Although, CIE-Lab and CIEDE2000 color changes evaluations generate different absolute values, it has been shown that changes in color follow similar trends [4].…”
Section: Discussionmentioning
confidence: 99%
“…However, the CIEDE2000 (∆E 00 ) is more indicated for small color changes when compared samples that have colors close together [2,20]. Although, CIE-Lab and CIEDE2000 color changes evaluations generate different absolute values, it has been shown that changes in color follow similar trends [4].…”
Section: Discussionmentioning
confidence: 99%
“…Endogenous contributing factors include material aging, type of initiator systems, duration of polymerization, resin matrix composition, conversion of the matrix monomers, particle size and hardness, material polishability, and oxidation of the unreacted carbon double bonds . Exogenous sources comprise of dietary and smoking habits . Knowledge of the optical properties of CAD/CAM composites is important to predict their long‐term clinical success.…”
Section: Introductionmentioning
confidence: 99%
“…Resin composite's mimetism toward the surrounding tooth structure, as well as the stability of the esthetic result, are important clinical parameters for a long‐lasting esthetic restoration. However, it is well‐known that resin composite restorations present change in optical properties with time . The magnitude of the optical degradation is influenced by factors related to the material, and by various abrasive/erosive challenges related to the oral hygiene, as well as the composition of the diet.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is well-known that resin composite restorations present change in optical properties with time. [1][2][3][4][5][6][7][8] The magnitude of the optical degradation is influenced by factors related to the material, and by various abrasive/erosive challenges related to the oral hygiene, as well as the composition of the diet. Studies have shown that, when in contact with staining agents, resin composites undergo sorption of extrinsic pigments, which is increased when these materials are exposed to alcoholic media (drinks and/or mouth rinses) and acidic media (drinks and biofilm) due to further degradation of the organic matrix.…”
Section: Introductionmentioning
confidence: 99%